Optical film, polarizing plate, and image display device

By using specific compounds (A) in the optical film and controlling their content and optical properties, the problem of phase difference changes in traditional optical films in high temperature environments is solved, and performance stability and reduction of highlight defects are achieved.

JP2025039526APending Publication Date: 2025-03-21SUMITOMO CHEM CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2024129113
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-09-08
Filing Date
2024-08-05
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The phase difference value of traditional optical films is easily changed in high temperature environments, resulting in unstable performance.

Method used

An optical film containing a specific compound (A) as a partial structure is used, and the content of compound A is between 1.5 kg/m³ and 20 kg/m³, and a specific optical performance formula is met to stabilize the phase difference value.

Benefits of technology

In a high temperature environment, the phase difference value of the optical film decreases, and the occurrence of bright spot defects is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025039526000001
    Figure 2025039526000001
  • Figure 2025039526000002
    Figure 2025039526000002
  • Figure 2025039526000003
    Figure 2025039526000003
Patent Text Reader

Abstract

To provide an optical film that exhibits little change in the phase difference value even when exposed to a high-temperature environment.SOLUTION: The optical film of the present disclosure contains a compound (A) having as a substructure a skeleton represented by the general formula (A1) in the figure. The content of the compound (A) per unit volume is from 1.5 kg / m3 to 20 kg / m3 inclusive. [In the formula (A1), R1 represents a hydrogen atom, a hydrocarbon group, or a carbonyl group.]SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to an optical film, a polarizing plate, and an image display device. [Background technology]

[0002] In flat panel displays (FPDs), members including optical films such as polarizing plates, retardation plates, etc. As such optical films, optical films formed using compositions including a polymerizable liquid crystal compound, a photopolymerization initiator, and a solvent are known (for example, Patent Document 1). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2012-214801 A Summary of the Invention [Problem to be solved by the invention]

[0004] Conventional optical films have a problem in that their retardation values ​​change when exposed to a high-temperature environment.

[0005] The present disclosure provides an optical film whose retardation value is unlikely to change even when exposed to a high-temperature environment. The present disclosure also provides a polarizing plate including such an optical film, and an image display device including the same. [Means for solving the problem]

[0006] In order to solve the above problems, the present disclosure provides the following optical film, polarizing plate, and image display device. [1] A compound (A) having a skeleton represented by the following general formula (A1) as a partial structure, The content of compound (A) per unit volume is 1.5 kg / m 3 More than 20kg / m 3 The following is an optical film. [ka] [In formula (A1), R 1 represents a hydrogen atom, a hydrocarbon group, or a carbonyl group. [2] The optical film according to [1], which satisfies the following formulas (1) and (2): 0.82≦Re(450) / Re(550)≦0.98 (1) 100nm≦Re(550)≦160nm (2) [In the formula, Re(450) represents an in-plane retardation value for light having a wavelength of 450 nm, and Re(550) represents an in-plane retardation value for light having a wavelength of 550 nm.] [3] The optical film according to [1] or [2], having a thickness of 0.5 μm or more and 5 μm or less. [4] The optical film according to any one of [1] to [3], which contains a cured product of a polymerizable liquid crystal compound. [5] A polarizing plate comprising a polarizing film and the optical film according to any one of [1] to [4]. [6] An image display device comprising the polarizing plate according to [5]. Effect of the Invention

[0007] According to the present disclosure, there is provided an optical film whose retardation value is unlikely to change even when exposed to a high-temperature environment. Also, according to the present disclosure, there is provided a polarizing plate including such an optical film and an image display device including the same. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] [Optical film] The optical film according to the present embodiment (hereinafter, also simply referred to as "optical film") contains a compound (A) (hereinafter, also simply referred to as "compound (A)") having a skeleton represented by the following general formula (A1) as a partial structure, and the content of the compound (A) per unit volume is 1.5 kg / m 3 More than 20kg / m 3 The following is the result.

[0009] [ka] [In formula (A1), R 1 represents a hydrogen atom, a hydrocarbon group, or a carbonyl group.

[0010] The optical film contains the compound (A) and the content is within the above-mentioned range, so that the change in retardation value is suppressed even when exposed to a high-temperature environment. In addition, such an optical film tends to be able to suppress the occurrence of bright spot defects caused by alignment defects.

[0011] The skeleton represented by the above general formula (A1) is a compound represented by the above general formula (A1) having a carbon atom, a nitrogen atom, and R 1 The skeleton consists of:

[0012] R 1 When is a hydrocarbon group, the hydrocarbon group may or may not have a branch. The number of carbon atoms in the hydrocarbon group may be 1 or more, 5 or more, or 8 or more, and 20 or less, 16 or less, or 10 or less. Examples of the hydrocarbon group include an alkyl group, an alkenyl group, an alkynyl group, an aryl group, and an aralkyl group. One or more hydrogen atoms in the hydrocarbon group may be substituted with a substituent. Examples of such a substituent include a hydroxyl group.

[0013] R 1 When is a carbonyl group, examples of the carbonyl group include a formyl group, an acetyl group, an ethylcarbonyl group, a butyryl group, a cyclohexylcarbonyl group, an allylcarbonyl group, a phenylcarbonyl group and a methylphenylcarbonyl group.

[0014] Since there is a tendency that the retardation value is less likely to change and the occurrence of bright spot defects is suppressed even when the optical film is exposed to a high-temperature environment, it is preferable that the compound (A) contained in the optical film has at least one of the substituents represented by the following general formulas (A11) to (A14).

[0015] [ka]

[0016] In the formulae (A11) to (A14), * represents a bond.

[0017] In formula (A11), R 11 represents a hydrocarbon group. The number of carbon atoms in the hydrocarbon group may be, for example, 1 to 20. In formula (A11), n11 represents an integer of 1 to 5.

[0018] In formula (A12), R 12 represents a hydrocarbon group. The hydrocarbon group may have, for example, 1 to 20 carbon atoms.

[0019] In formula (A13), R 13 represents a hydrocarbon group. The number of carbon atoms in the hydrocarbon group may be, for example, 1 to 20. In formula (A13), n13 represents an integer of 1 to 5.

[0020] In formula (A14), R 14 represents a hydrocarbon group having no fluorine atom or a hydrocarbon group having a fluorine atom. The number of carbon atoms in the hydrocarbon group may be, for example, 1 to 20. In formula (A14), n14 represents an integer of 1 to 5.

[0021] Since there is a tendency that the retardation value is less likely to change and the occurrence of bright spot defects is suppressed even when the optical film is exposed to a high-temperature environment, the compound (A) contained in the optical film is preferably a compound having a group represented by any one of the following formulas (A21) to (A23), and more preferably a compound having a group represented by the following formula (A21). In the formulas (A21) to (A23), * represents a bond.

[0022] [ka]

[0023] Since the retardation value tends to be less likely to change and the occurrence of bright spot defects tends to be suppressed even when the optical film is exposed to a high-temperature environment, the compound (A) contained in the optical film is preferably a compound derived from the compounds represented by the following formulas (A31) to (A37) and the compounds represented by the following formulas (A31) to (A33), and more preferably a compound derived from the compound represented by the following formula (A31) and the compound represented by the following formula (A31).

[0024] [ka]

[0025] [ka]

[0026] Even when the optical film is exposed to a high-temperature environment, the retardation value is less likely to change, and the occurrence of bright spot defects tends to be suppressed. Therefore, the CLogP of the compound (A) contained in the optical film is preferably 1 to 30, more preferably 9 to 20. CLogP is a value that estimates the affinity of an organic compound to water and 1-octanol [P=(concentration of the organic compound in the 1-octanol phase) / (concentration of the organic compound in the water phase)], and can be calculated by a calculation program using fragment values ​​of atomic groups determined by the number of atoms constituting the compound and the type of chemical bond. In this specification, CLogP means a value calculated by ChemDraw ver. 18.2 of PerkinElmer.

[0027] The content of compound (A) per unit volume of the optical film is 1.5 kg / m 3The content is 5.0 kg / m or more because the retardation value of the obtained optical film is less likely to change even when exposed to a high-temperature environment and the occurrence of bright spot defects tends to be suppressed. 3 The content of the compound (A) per unit volume of the optical film is preferably 20 kg / m or more. 3 The content is 18 kg / m or less because the retardation value of the obtained optical film is less likely to change even when exposed to a high-temperature environment and the occurrence of bright spot defects tends to be suppressed. 3 It is preferable that:

[0028] The optical film preferably contains at least one of a cured product and an uncured product of a polymerizable liquid crystal compound in addition to the compound (A). The optical film may be a cured product of a polymerizable liquid crystal composition containing the polymerizable liquid crystal compound and the compound (A). The compound (A) may have functions such as a leveling agent, an antioxidant, a polymerization initiator, and a colorant in the polymerizable liquid crystal composition.

[0029] The content of the cured polymerizable liquid crystal compound may be 70% by mass or more, 80% by mass or more, 90% by mass or more, or 95% by mass or more based on the total amount of the optical film.

[0030] In the present specification, the polymerizable liquid crystal compound means a liquid crystal compound having a polymerizable group, particularly a photopolymerizable group. As the polymerizable liquid crystal compound, for example, a polymerizable liquid crystal compound conventionally known in the field of retardation films can be used.

[0031] The polymerizable group refers to a group that can participate in a polymerization reaction. The photopolymerizable group refers to a polymerizable group that can participate in a polymerization reaction by a reactive species generated from a photopolymerization initiator, such as an active radical or an acid. Examples of the photopolymerizable group include a vinyl group, a vinyloxy group, a 1-chlorovinyl group, an isopropenyl group, a 4-vinylphenyl group, an acryloyloxy group, a methacryloyloxy group, an oxiranyl group, and an oxetanyl group. Among them, an acryloyloxy group, a methacryloyloxy group, a vinyloxy group, an oxiranyl group, and an oxetanyl group are preferred, and an acryloyloxy group is more preferred. The liquid crystal property exhibited by the polymerizable liquid crystal compound may be a thermotropic liquid crystal or a lyotropic liquid crystal, but a thermotropic liquid crystal is preferred in terms of the ability to precisely control the film thickness. In addition, the phase order structure in the thermotropic liquid crystal may be a nematic liquid crystal or a smectic liquid crystal. The polymerizable liquid crystal compound may be used alone or in combination of two or more kinds.

[0032] The polymerizable liquid crystal compound is preferably a compound having the following characteristics (1) to (4). (1) A compound capable of forming a nematic phase or a smectic phase. (2) The polymerizable liquid crystal compound has π electrons in the long axis direction (a). (3) It has π electrons in a direction intersecting the long axis direction (a) [intersecting direction (b)]. (4) The total number of π electrons present in the long axis direction (a) is N(πa), and the total number of molecular weights present in the long axis direction is N(Aa), where N(πa) is the total number of π electrons present in the long axis direction, and N(Aa) is the total number of molecular weights present in the long axis direction. The π electron density in the long axis direction (a) of a polymerizable liquid crystal compound is defined by the following formula (i): D(πa)=N(πa) / N(Aa) (i) The total number of π electrons present in the cross direction (b) is N(πb), and the total number of molecular weights present in the cross direction (b) is N(Ab), where N(πb) is the total number of π electrons present in the cross direction (b), and the π electron density in the cross direction (b) of the polymerizable liquid crystal compound is defined by the following formula (ii): D(πb)=N(πb) / N(Ab) (ii) and the formula (iii) 0≦[D(πa) / D(πb)]<1 (iii) [That is, the π electron density in the intersecting direction (b) is greater than the π electron density in the long axis direction (a)]. As described above, the polymerizable liquid crystal compound having π electrons on the long axis and in the direction intersecting therewith has, for example, a T-shaped structure.

[0033] The polymerizable liquid crystal compound is preferably a compound capable of forming a nematic phase. In the above features (1) to (4), the long axis direction (a) and the number of π electrons N are defined as follows. The long axis direction (a) is, for example, in the case of a compound having a rod-like structure, the long axis direction of the rod. The number of π electrons present in the long axis direction (a), N(πa), does not include the π electrons lost due to the polymerization reaction. The number of π electrons present along the long axis (a), N(πa), is the total number of π electrons on the long axis and those conjugated with it, and includes, for example, the number of π electrons present in rings present along the long axis (a) that satisfy Hückel's rule. The number of π electrons present in the intersecting direction (b), N(πb), does not include the π electrons lost due to the polymerization reaction. A polymerizable liquid crystal compound that satisfies the above conditions has a mesogenic structure in the long axis direction, and this mesogenic structure allows the compound to exhibit a liquid crystal phase (nematic phase, smectic phase).

[0034] The polymerizable liquid crystal compound satisfying the above (1) to (4) can form a nematic phase or a smectic phase by coating on a photo-alignment film described later and heating to a phase transition temperature or higher. In the nematic phase or smectic phase formed by the alignment of the polymerizable liquid crystal compound, for example, the long axis directions of the polymerizable liquid crystal compound are aligned so as to be parallel to each other, and the long axis direction is the alignment direction of the nematic phase. When such a polymerizable liquid crystal compound is made into a film and polymerized in the nematic or smectic phase state, a polymer film can be formed of a polymer polymerized in a state of being aligned in the long axis direction (a). This polymer film absorbs ultraviolet light by π electrons in the long axis direction (a) and π electrons in the cross direction (b).

[0035] Here, the maximum absorption wavelength of ultraviolet light absorbed by π electrons in the cross direction (b) is defined as λbmax. λbmax is usually 300 nm to 400 nm. The density of π electrons satisfies the above formula (iii), and the π electron density in the cross direction (b) is greater than the π electron density in the long axis direction (a), so that the polymer film has a higher absorption of linearly polarized ultraviolet light (wavelength λbmax) having a vibration plane in the cross direction (b) than linearly polarized ultraviolet light (wavelength λbmax) having a vibration plane in the long axis direction (a). The ratio (the ratio of absorbance in the cross direction (b) of linearly polarized ultraviolet light / absorbance in the long axis direction (a)) is, for example, more than 1.0, preferably 1.2 or more and 30 or less, for example, 10 or less.

[0036] The polymerizable liquid crystal compound having the above characteristics generally exhibits reverse wavelength dispersion. Specifically, for example, a polymerizable liquid crystal compound represented by the following formula (X): [ka] Examples of the compound include compounds represented by the following formula:

[0037] In formula (X), Ar represents a divalent aromatic group which may have a substituent. Here, the aromatic group means a group having an aromatic ring in which the number of π electrons in the ring structure is [4n+2] according to the Huckel rule. Here, n represents an integer. When a ring structure is formed by including heteroatoms such as -N= or -S-, the non-covalent bond electron pairs on these heteroatoms also satisfy the Huckel rule and have aromaticity. The aromatic group preferably contains at least one of a nitrogen atom, an oxygen atom, and a sulfur atom. The aromatic ring contained in Ar may be one or more. When the aromatic ring contained in Ar is two or more, the two or more aromatic rings may be bonded to each other by a divalent bond group such as a single bond, -CO-O-, or -O-.

[0038] G 1 and G 2each independently represents a divalent aromatic group or a divalent alicyclic hydrocarbon group, wherein a hydrogen atom contained in the divalent aromatic group or the divalent alicyclic hydrocarbon group may be substituted with a halogen atom, an alkyl group having 1 to 4 carbon atoms, a fluoroalkyl group having 1 to 4 carbon atoms, an alkoxy group having 1 to 4 carbon atoms, a cyano group, or a nitro group, and a carbon atom constituting the divalent aromatic group or the divalent alicyclic hydrocarbon group may be substituted with an oxygen atom, a sulfur atom, or a nitrogen atom.

[0039] G 1 and G 2 are preferably each independently a 1,4-phenylenediyl group which may be substituted with at least one substituent selected from the group consisting of a halogen atom and an alkyl group having 1 to 4 carbon atoms, or a 1,4-cyclohexanediyl group which may be substituted with at least one substituent selected from the group consisting of a halogen atom and an alkyl group having 1 to 4 carbon atoms, more preferably a 1,4-phenylenediyl group substituted with a methyl group, an unsubstituted 1,4-phenylenediyl group, or an unsubstituted 1,4-trans-cyclohexanediyl group, and even more preferably an unsubstituted 1,4-phenylenediyl group or an unsubstituted 1,4-trans-cyclohexanediyl group. In addition, there are multiple G 1 and G 2 At least one of L is preferably a divalent alicyclic hydrocarbon group. 1 Or L 2 G binds to 1 and G 2 It is more preferable that at least one of the groups is a divalent alicyclic hydrocarbon group.

[0040] L 1 , L 2 , B 1 and B. 2 are each independently a single bond or a divalent linking group.

[0041] L 1 and L 2 are each independently preferably a single bond, an alkylene group having 1 to 4 carbon atoms, -O-, -S-, -Ra1 OR a2 -, -R a3 COOR a4 -, -R a5 O.C.O.R. a6 -, R a7 OC=OOR a8 -, -N=N-, -CR c =CR d - or -C≡C-, where R a1 ~R a8 each independently represents a single bond or an alkylene group having 1 to 4 carbon atoms; R c and R d represents an alkyl group having 1 to 4 carbon atoms or a hydrogen atom. 1 and L 2 are each independently preferably a single bond, -OR a2-1 -, -CH2-, -CH2CH2-, -COOR a4-1 - or OCOR a6-1 -, where R a2-1 , R a4-1 and Ra 6-1 Each independently represents a single bond, -CH-, or -CHCH-. 1 and L 2 are each independently more preferably a single bond, -O-, -CH2CH2-, -COO-, -COOCH2CH2- or OCO-.

[0042] B 1 and B. 2 are each independently preferably a single bond, an alkylene group having 1 to 4 carbon atoms, -O-, -S-, -R a9 OR a10 -, -R a11 COOR a12 -, -R a13 O.C.O.R. a14 - or R a15 OC=OOR a16 -It is. a9 ~R a16 each independently represents a single bond or an alkylene group having 1 to 4 carbon atoms. 1 and B. 2 are each independently preferably a single bond, -OR a10-1-, -CH2-, -CH2CH2-, -COOR a12-1 - or OCOR a14-1 -, where R a10-1 , R a12-1 and R a14-1 Each independently represents a single bond, -CH-, or -CHCH-. 1 and B. 2 are each independently more preferably a single bond, -O-, -CH2CH2-, -COO-, -COOCH2CH2-, -OCO- or OCOCH2CH2-.

[0043] k and l each independently represent an integer of 0 to 3, and satisfy the relationship of 1≦k+l. Here, when 2≦k+l, a plurality of B 1 , B 2 , G 1 and G 2 may be the same as or different from each other.

[0044] From the viewpoint of expressing reverse wavelength dispersion, k and l are preferably in the range of 2≦k+l≦6, preferably k+l=4, and more preferably k=2 and l=2. When k=2 and l=2, a symmetrical structure is obtained, which is preferable.

[0045] E 1 and E 2 Each of E independently represents an alkanediyl group having 1 to 17 carbon atoms. 1 and E 2 is more preferably an alkanediyl group having 4 to 12 carbon atoms. Furthermore, a hydrogen atom contained in the alkanediyl group may be substituted with a halogen atom, and -CH2- contained in the alkanediyl group may be substituted with -O-, -S-, -SiH2- or -C(=O)-.

[0046] P 1 and P 2 each independently represents a polymerizable group or a hydrogen atom, and at least one of them is a polymerizable group.

[0047] P 1 Or P 2Examples of the polymerizable group represented by the formula (I) include an epoxy group, a vinyl group, a vinyloxy group, a 1-chlorovinyl group, an isopropenyl group, a 4-vinylphenyl group, an acryloyloxy group, a methacryloyloxy group, an oxiranyl group, and an oxetanyl group. Among these, an acryloyloxy group, a methacryloyloxy group, a vinyloxy group, an oxiranyl group, and an oxetanyl group are preferred, and an acryloyloxy group is more preferred.

[0048] It is preferable that Ar has at least one selected from the group consisting of an aromatic hydrocarbon ring which may have a substituent, an aromatic heterocycle which may have a substituent, and an electron-withdrawing group. Examples of the aromatic hydrocarbon ring include a benzene ring, a naphthalene ring, and an anthracene ring, and the like, and the benzene ring and the naphthalene ring are preferable. Examples of the aromatic heterocycle include a furan ring, a benzofuran ring, a pyrrole ring, an indole ring, a thiophene ring, a benzothiophene ring, a pyridine ring, a pyrazine ring, a pyrimidine ring, a triazole ring, a triazine ring, a pyrroline ring, an imidazole ring, a pyrazole ring, a thiazole ring, a benzothiazole ring, a thienothiazole ring, an oxazole ring, a benzoxazole ring, and a phenanthroline ring. Among them, it is preferable to have a thiazole ring, a benzothiazole ring, or a benzofuran ring, and it is more preferable to have a benzothiazole group. In addition, when Ar contains a nitrogen atom, it is preferable that the nitrogen atom has a π electron.

[0049] In formula (X), the total number Nπ of π electrons contained in the divalent aromatic group represented by Ar is preferably 8 or more, more preferably 10 or more, even more preferably 14 or more, and particularly preferably 16 or more. Also, it is preferably 30 or less, more preferably 26 or less, and even more preferably 24 or less.

[0050] Examples of the aromatic group represented by Ar include the following groups.

[0051] [ka]

[0052] In formulae (Ar-1) to (Ar-23), * represents a bond; Z 0 , Z 1 and Z 2 each independently represents a hydrogen atom, a halogen atom, an alkyl group having 1 to 12 carbon atoms, a cyano group, a nitro group, an alkylsulfinyl group having 1 to 12 carbon atoms, an alkylsulfonyl group having 1 to 12 carbon atoms, a carboxyl group, a fluoroalkyl group having 1 to 12 carbon atoms, an alkoxy group having 1 to 12 carbon atoms, an alkylthio group having 1 to 12 carbon atoms, an N-alkylamino group having 1 to 12 carbon atoms, an N,N-dialkylamino group having 2 to 12 carbon atoms, an N-alkylsulfamoyl group having 1 to 12 carbon atoms, or an N,N-dialkylsulfamoyl group having 2 to 12 carbon atoms. 0 , Z 1 and Z 2 may contain a polymerizable group.

[0053] Q 1 and Q 2 are each independently -CR 21 R 22 -, -S-, -NH-, -NR 21 represents -, -CO- or -O-; R 21 and R 22 each independently represents a hydrogen atom or an alkyl group having 1 to 4 carbon atoms.

[0054] Q 1 and Q 2 -NH-, -S-, -NR 21 - and -O- are preferred. 21 is preferably a hydrogen atom. 1 and Q 2 is more preferably -S-, -O- or -NH-.

[0055] J 1 and J 2 each independently represents a carbon atom or a nitrogen atom.

[0056] Y 1 , Y 2 and Y 3each independently represents an optionally substituted aromatic hydrocarbon group or an optionally substituted aromatic heterocyclic group.

[0057] W 1 and W 2 each independently represents a hydrogen atom, a cyano group, a methyl group or a halogen atom; and m represents an integer of 0 to 6.

[0058] Y 1 , Y 2 and Y 3 Examples of the aromatic hydrocarbon group in the formula (I) include aromatic hydrocarbon groups having 6 to 20 carbon atoms, such as a phenyl group, a naphthyl group, an anthryl group, a phenanthryl group, and a biphenyl group, of which a phenyl group and a naphthyl group are preferred, and a phenyl group is more preferred. Examples of the aromatic heterocyclic group in the formula (I) include aromatic heterocyclic groups having 4 to 20 carbon atoms and containing at least one heteroatom, such as a nitrogen atom, an oxygen atom, or a sulfur atom, such as a furyl group, a pyrrolyl group, a thienyl group, a pyridinyl group, a thiazolyl group, and a benzothiazolyl group, of which a furyl group, a thienyl group, a pyridinyl group, a thiazolyl group, and a benzothiazolyl group are preferred.

[0059] Y 1 , Y 2 and Y 3 may each independently be an optionally substituted polycyclic aromatic hydrocarbon group or polycyclic aromatic heterocyclic group. The polycyclic aromatic hydrocarbon group refers to a condensed polycyclic aromatic hydrocarbon group or a group derived from an aromatic ring assembly. The polycyclic aromatic heterocyclic group refers to a condensed polycyclic aromatic heterocyclic group or a group derived from an aromatic ring assembly.

[0060] Z 0 , Z 1 and Z 2 are each preferably independently a hydrogen atom, a halogen atom, an alkyl group having 1 to 12 carbon atoms, a cyano group, a nitro group, or an alkoxy group having 1 to 12 carbon atoms; Z 0 is preferably a hydrogen atom, an alkyl group having 1 to 12 carbon atoms, or a cyano group; Z 1 and Z 2 is more preferably a hydrogen atom, a fluorine atom, a chlorine atom, a methyl group, or a cyano group. 0 , Z1 and Z 2 may contain a polymerizable group.

[0061] Among the formulae (Ar-1) to (Ar-23), the formulae (Ar-6) and (Ar-7) are preferred from the viewpoint of molecular stability.

[0062] In formulas (Ar-16) to (Ar-23), Y 1 is the nitrogen atom to which it is bonded and Z 0 and may form an aromatic heterocyclic group. Examples of the aromatic heterocyclic group that Ar may have include those mentioned above, such as a pyrrole ring, an imidazole ring, a pyrroline ring, a pyridine ring, a pyrazine ring, a pyrimidine ring, an indole ring, a quinoline ring, an isoquinoline ring, a purine ring, and a pyrrolidine ring. This aromatic heterocyclic group may have a substituent. In addition, Y 1 is the nitrogen atom to which it is bonded and Z 0 In addition, it may be the above-mentioned optionally substituted polycyclic aromatic hydrocarbon group or polycyclic aromatic heterocyclic group, for example, a benzofuran ring, a benzothiazole ring, or a benzoxazole ring.

[0063] The content of the polymerizable liquid crystal compound in the polymerizable liquid crystal composition is, for example, 70 to 99.5 parts by mass, preferably 80 to 99 parts by mass, more preferably 85 to 98 parts by mass, and even more preferably 90 to 95 parts by mass, based on 100 parts by mass of the solid content of the polymerizable liquid crystal composition. If the content of the polymerizable liquid crystal compound is within the above range, it is advantageous in terms of the alignment of the obtained liquid crystal cured film. In this specification, the solid content of the polymerizable liquid crystal composition means all components excluding volatile components such as organic solvents from the polymerizable liquid crystal composition.

[0064] The polymerizable liquid crystal composition contains a compound (A). Since the retardation value tends to be less likely to change and the occurrence of bright spot defects tends to be suppressed even when the obtained optical film is exposed to a high-temperature environment, the content of the compound (A) in the polymerizable liquid crystal composition is, for example, 1 to 20 parts by mass, preferably 3 to 12 parts by mass, and more preferably 5 to 10 parts by mass relative to 100 parts by mass of the solid content of the polymerizable liquid crystal composition.

[0065] The polymerizable liquid crystal composition may further contain, in addition to the polymerizable liquid crystal compound and the compound (A), additives such as a solvent, a photopolymerization initiator, a leveling agent, an antioxidant, a photosensitizer, etc. Each of these components may be used alone or in combination of two or more.

[0066] Since the polymerizable liquid crystal composition is usually applied to a substrate or the like in a state of being dissolved in a solvent, it is preferable that the composition contains a solvent. The solvent is preferably a solvent capable of dissolving the polymerizable liquid crystal compound and is preferably a solvent inactive to the polymerization reaction of the polymerizable liquid crystal compound. Examples of the solvent include alcohol solvents such as water, methanol, ethanol, ethylene glycol, isopropyl alcohol, propylene glycol, ethylene glycol methyl ether, ethylene glycol butyl ether, 1-methoxy-2-propanol, 2-butoxyethanol, and propylene glycol monomethyl ether; ester solvents such as ethyl acetate, butyl acetate, ethylene glycol methyl ether acetate, γ-butyrolactone, propylene glycol methyl ether acetate, and ethyl lactate; ketone solvents such as acetone, methyl ethyl ketone, cyclopentanone, cyclohexanone, 2-heptanone, and methyl isobutyl ketone; aliphatic hydrocarbon solvents such as pentane, hexane, and heptane; alicyclic hydrocarbon solvents such as ethylcyclohexane; aromatic hydrocarbon solvents such as toluene and xylene; nitrile solvents such as acetonitrile; ether solvents such as tetrahydrofuran and dimethoxyethane; chlorine-containing solvents such as chloroform and chlorobenzene; and amide solvents such as dimethylacetamide, dimethylformamide, N-methyl-2-pyrrolidone (NMP), and 1,3-dimethyl-2-imidazolidinone. These solvents can be used alone or in combination of two or more. Among these, alcohol solvents, ester solvents, ketone solvents, chlorine-containing solvents, amide solvents and aromatic hydrocarbon solvents are preferred.

[0067] The content of the solvent in the polymerizable liquid crystal composition is preferably 50 to 98 parts by weight, more preferably 70 to 95 parts by weight, relative to 100 parts by weight of the polymerizable liquid crystal composition. Therefore, the solid content per 100 parts by weight of the polymerizable liquid crystal composition is preferably 2 to 50 parts by weight. If the solid content is 50 parts by weight or less, the viscosity of the polymerizable liquid crystal composition is low, so that the thickness of the film becomes approximately uniform and unevenness tends to be less likely to occur. The solid content can be appropriately determined in consideration of the thickness of the liquid crystal cured film to be produced.

[0068] The polymerization initiator is a compound that generates reactive species by the contribution of heat or light and can initiate a polymerization reaction of a polymerizable liquid crystal compound, etc. Examples of the reactive species include active species such as radicals, cations, and anions. Among them, a photopolymerization initiator that generates radicals by light irradiation is preferred from the viewpoint of easy reaction control.

[0069] Examples of the photopolymerization initiator include benzoin compounds, benzophenone compounds, benzil ketal compounds, oxime compounds, α-hydroxyketone compounds, α-aminoketone compounds, triazine compounds, iodonium salts, and sulfonium salts.

[0070] The content of the photopolymerization initiator is, for example, 0.1 to 30 parts by mass, preferably 1 to 20 parts by mass, and more preferably 1 to 15 parts by mass, relative to 100 parts by mass of the polymerizable liquid crystal compound. Within the above range, the reaction of the polymerizable group proceeds sufficiently, and the alignment of the polymerizable liquid crystal compound is unlikely to be disturbed.

[0071] The leveling agent is an additive that has the function of adjusting the fluidity of the polymerizable liquid crystal composition and making the coating film obtained by applying the composition flatter. Examples of the leveling agent include silicone-based, polyacrylate-based and perfluoroalkyl-based leveling agents. As the leveling agent, a commercially available product may be used. Specific examples of the leveling agent include DC3PA, SH7PA, DC11PA, SH28PA, SH29PA, SH30PA, ST80PA, ST86PA, SH8400, SH8700, FZ2123 (all manufactured by Dow Corning Toray Co., Ltd.), KP321, KP323, KP324, KP326, KP340, KP341, X22-161A, KF6001 (all manufactured by Shin-Etsu Chemical Co., Ltd.), TSF400, TSF401, TSF410, TSF4300, TSF4440, TSF4445, TSF-4446, TSF4452, TSF4460 (all manufactured by Momentive Performance Materials Co., Ltd.). Japan LLC), Fluorinert (registered trademark) FC-72, FC-40, FC-43, FC-3283 (all manufactured by Sumitomo 3M Limited), Megafac (registered trademark) R-08, R-30, R-90, F-410, F-411, F-443, F-445, F-470, F-477, F-479, F-482, F-483 (all manufactured by DIC Corporation), F-top (trade name) EF301, EF303, Examples of the leveling agent include EF351, EF352 (all manufactured by Mitsubishi Materials Electronics Co., Ltd.), Surflon (registered trademark) S-381, S-382, S-383, S-393, SC-101, SC-105, KH-40, and SA-100 (all manufactured by AGC Seimi Chemical Co., Ltd.), trade names E1830 and E5844 (manufactured by Daikin Fine Chemical Research Institute Co., Ltd.), BM-1000, BM-1100, BYK-352, BYK-353, and BYK-361N (all trade names: manufactured by BM Chemie Co., Ltd.). The leveling agent can be used alone or in combination of two or more kinds.

[0072] The content of the leveling agent is preferably 0.01 to 5 parts by mass, more preferably 0.05 to 3 parts by mass, based on 100 parts by mass of the polymerizable liquid crystal compound. When the content of the leveling agent is within the above range, the obtained liquid crystal cured film tends to be smoother, which is preferable.

[0073] By blending an antioxidant, the polymerization reaction of the polymerizable liquid crystal compound can be controlled. The antioxidant may be a primary antioxidant selected from phenol-based antioxidants, amine-based antioxidants, quinone-based antioxidants, and nitroso-based antioxidants, or a secondary antioxidant selected from phosphorus-based antioxidants and sulfur-based antioxidants. In order to polymerize the polymerizable liquid crystal compound without disturbing the alignment of the polymerizable liquid crystal compound, the content of the antioxidant is, for example, 0.01 to 10 parts by mass, preferably 0.1 to 5 parts by mass, and more preferably 0.1 to 3 parts by mass, relative to 100 parts by mass of the polymerizable liquid crystal compound. The antioxidant may be used alone or in combination of two or more kinds.

[0074] In addition, the photosensitizer can be used to increase the sensitivity of the photopolymerization initiator. Examples of the photosensitizer include xanthones such as xanthone and thioxanthone; anthracenes having a substituent such as anthracene and alkyl ether; phenothiazine; and rubrene. The photosensitizer can be used alone or in combination of two or more kinds. The content of the photosensitizer is, for example, 0.01 to 10 parts by mass, preferably 0.05 to 5 parts by mass, and more preferably 0.1 to 3 parts by mass, relative to 100 parts by mass of the polymerizable liquid crystal compound.

[0075] The polymerizable liquid crystal composition can be obtained by stirring the compound (A), the polymerizable liquid crystal compound, and components other than the polymerizable liquid crystal compound such as a solvent at a predetermined temperature.

[0076] The optical film is produced, for example, as follows. That is, first, a coating film of a polymerizable liquid crystal composition is formed. The polymerizable liquid crystal compound is aligned in the horizontal direction with respect to the plane of the coating film. The polymerizable liquid crystal composition is cured while maintaining the horizontal alignment state of the polymerizable liquid crystal compound. In this way, an optical film is produced. As a method for aligning the polymerizable liquid crystal compound in the horizontal direction, for example, a method of applying a polymerizable liquid crystal composition containing a rod-shaped polymerizable liquid crystal compound that is easily aligned horizontally onto a horizontal alignment film described later can be mentioned.

[0077] The optical film preferably satisfies the following formulas (1) and (2). When the optical film satisfies these formulas, when a circular polarizing plate including the optical film is used in an organic EL display device, the reflection hue is improved and coloring during black display tends to be less likely to occur. 0.82≦Re(450) / Re(550)≦0.98 (1) [In the formula, Re(450) represents an in-plane retardation value for light having a wavelength of 450 nm, and Re(550) represents an in-plane retardation value for light having a wavelength of 550 nm.] 100nm≦Re(550)≦160nm (2) [In the formula, Re(550) represents an in-plane retardation value for light having a wavelength of 550 nm.]

[0078] From the same viewpoint, Re(450) / Re(550) is preferably 0.70 or more, more preferably 0.78 or more, and is preferably 0.95 or less, more preferably 0.92 or less.

[0079] From the same viewpoint, Re(550) is preferably 130 nm or more and 150 nm or less.

[0080] Re(450) may be 110 nm or more and may be 130 nm or less.

[0081] Re(630) may be 130 nm or more and 150 nm or less.

[0082] Re(630) / Re(550) may be 0.95 or more and 1.05 or less, where Re(630) represents an in-plane retardation value for light having a wavelength of 630 nm.

[0083] The in-plane retardation value is determined by the following formula (3). Therefore, the in-plane retardation value (Re(λ): in-plane retardation value of the optical film at wavelength λ(nm)) is adjusted by changing the three-dimensional refractive index and thickness d. The three-dimensional refractive index depends on the molecular structure and orientation state of the polymerizable liquid crystal compound.

[0084] Re(λ)=(nx(λ)-ny(λ))×d (3) [In the formula, nx(λ) represents the principal refractive index at wavelength λ in the plane of the optical film, ny(λ) represents the refractive index at wavelength λ in the same plane as nx and in a direction perpendicular to the direction of nx, and d represents the thickness of the optical film.]

[0085] The thickness of the optical film is preferably 0.5 to 5.0 μm, more preferably 0.8 to 4 μm, and further preferably 1.0 to 3.5 μm.

[0086] [Laminate] The laminate according to this embodiment (hereinafter, simply referred to as "laminate") includes the optical film according to the above embodiment and a horizontal alignment film. The optical film can also be called a horizontal alignment liquid crystal cured film in the laminate.

[0087] (horizontal alignment film) The horizontal alignment film has an alignment regulating force that aligns the polymerizable liquid crystal compound in the horizontal direction with respect to the film plane of the liquid crystal cured film. The alignment regulating force can be arbitrarily adjusted by the type of alignment film, the surface state, the rubbing conditions, etc., and when the alignment film is formed of a photoalignable polymer, it can be arbitrarily adjusted by the polarized light irradiation conditions, etc.

[0088] The horizontal alignment film is preferably one that has solvent resistance such that the polymerizable liquid crystal composition is not dissolved by application or the like, and has heat resistance in the heat treatment for removing the solvent and for aligning the polymerizable liquid crystal compound described below. Examples of the horizontal alignment film include a rubbed alignment film, a photo-aligned film, and a groove alignment film having an uneven pattern or a plurality of grooves on the surface. From the viewpoint of the accuracy of the alignment angle and the quality, a photo-aligned film is preferable.

[0089] The rubbed alignment film is produced, for example, as follows. That is, a composition containing an alignment polymer and a solvent (hereinafter also referred to as an "alignment polymer composition") is prepared. The alignment polymer composition is applied to the surface of a substrate, and the solvent is removed to obtain a coating film. The coating film is rubbed to impart an alignment control force. In this way, a rubbed alignment film is obtained. Examples of the solvent include the same solvents that can be contained in the polymerizable liquid crystal composition.

[0090] Examples of the oriented polymer include polyamides and gelatins having an amide bond in the molecule, polyimides having an imide bond in the molecule, and polyamic acids, which are hydrolyzates thereof, polyvinyl alcohol, alkyl-modified polyvinyl alcohol, polyacrylamide, polyoxazole, polyethyleneimine, polystyrene, polyvinylpyrrolidone, polyacrylic acid, and polyacrylic acid esters. Among these, polyvinyl alcohol is preferred. The oriented polymers can be used alone or in combination of two or more kinds.

[0091] The concentration of the orienting polymer in the orienting polymer composition may be within a range in which the orienting polymer material can be completely dissolved in the solvent, and is preferably 0.1 to 20%, more preferably 0.1 to 10%, calculated as solid content relative to the solution.

[0092] As the oriented polymer composition, a commercially available alignment film material may be used as it is. Examples of commercially available alignment film materials include Sunever (registered trademark, manufactured by Nissan Chemical Industries, Ltd.) and Optomer (registered trademark, manufactured by JSR Corporation).

[0093] The photo-alignment film is produced, for example, as follows. That is, a composition (hereinafter also referred to as "photo-alignment film-forming composition") containing at least one of a polymer and a monomer having a photoreactive group and a solvent is prepared. The photo-alignment film-forming composition is applied to the surface of a substrate, and the solvent is removed to obtain a coating film. Polarized light is irradiated onto the coating film. This results in a photo-alignment film.) Photo-alignment films are also advantageous in that the direction of the alignment regulating force can be arbitrarily controlled by selecting the polarization direction of the irradiated polarized light.

[0094] The photoreactive group refers to a group that generates liquid crystal alignment ability by irradiation with light. Specifically, it includes groups involved in photoreactions that are the origin of liquid crystal alignment ability, such as molecular alignment induction or isomerization reaction, dimerization reaction, photocrosslinking reaction or photodecomposition reaction, which are generated by irradiation with light. Among them, groups involved in dimerization reaction or photocrosslinking reaction are preferred in terms of excellent alignment ability. As the photoreactive group, a group having an unsaturated bond, particularly a double bond, is preferred, and a group having at least one selected from the group consisting of a carbon-carbon double bond (C=C bond), a carbon-nitrogen double bond (C=N bond), a nitrogen-nitrogen double bond (N=N bond) and a carbon-oxygen double bond (C=O bond) is particularly preferred.

[0095] Examples of photoreactive groups having a C=C bond include vinyl groups, polyene groups, stilbene groups, stilbazolyl groups, stilbazolium groups, chalcone groups, and cinnamoyl groups. Examples of photoreactive groups having a C=N bond include groups having structures such as aromatic Schiff bases and aromatic hydrazones. Examples of photoreactive groups having an N=N bond include azobenzene groups, azonaphthalene groups, aromatic heterocyclic azo groups, bisazo groups, formazan groups, and groups having an azoxybenzene structure. Examples of photoreactive groups having a C=O bond include benzophenone groups, coumarin groups, anthraquinone groups, and maleimide groups. These groups may have substituents such as alkyl groups, alkoxy groups, aryl groups, allyloxy groups, cyano groups, alkoxycarbonyl groups, hydroxyl groups, sulfonic acid groups, and halogenated alkyl groups.

[0096] The photoreactive group is preferably a photoreactive group involved in a photodimerization reaction, and a cinnamoyl group or a chalcone group is preferred in that the amount of polarized light irradiation required for photoalignment is relatively small, and a photoalignment film excellent in thermal stability and stability over time is easily obtained. As the photoreactive group-containing polymer for forming the horizontal alignment film, when the horizontal alignment liquid crystal cured film is formed from a polymerizable liquid crystal compound having a (meth)acryloyloxy group as a polymerizable group, the polymer is particularly preferably one having a cinnamoyl group such that the terminal of the polymer side chain has a cinnamic acid structure, since the adhesion with the horizontal alignment liquid crystal cured film can be further improved.

[0097] Examples of the solvent contained in the composition for forming a photo-alignment film include the same solvents as those contained in the polymerizable liquid crystal composition. The solvent can be appropriately selected depending on the solubility of the polymer or monomer having a photoreactive group.

[0098] The content of the polymer or monomer having a photoreactive group in the composition for forming a photo-alignment film can be appropriately adjusted depending on the type of the polymer or monomer and the thickness of the desired photo-alignment film. The content is preferably at least 0.2% by mass, more preferably 0.3 to 10% by mass, based on the mass of the composition for forming a photo-alignment film. In addition, the polymer forming the photo-alignment film is preferably a (meth)acrylic polymer, because it is easy to manufacture and can improve adhesion with the horizontally aligned liquid crystal cured film when the horizontally aligned liquid crystal cured film is formed from a polymerizable liquid crystal compound having a (meth)acryloyloxy group as a polymerizable group. The composition for forming a photo-alignment film may contain a polymer material such as polyvinyl alcohol or polyimide, or a photosensitizer, within a range in which the properties of the photo-alignment film are not significantly impaired.

[0099] A groove alignment film is a film that has a concave-convex pattern or multiple grooves on the film surface. When a polymerizable liquid crystal compound is applied to a film that has multiple linear grooves arranged at equal intervals, the liquid crystal molecules are aligned in the direction along the grooves.

[0100] The thickness of the alignment film (alignment film containing an orienting polymer or photoalignment film) is, for example, 10 to 10,000 nm, preferably 10 to 1,000 nm, more preferably 10 to 500 nm or less, further preferably 10 to 300 nm, and particularly preferably 50 to 250 nm.

[0101] (cured resin layer) The laminate may include a cured resin layer, the thickness of which is 0.1 to 10 μm, preferably 0.5 to 5 μm, from the viewpoint of making the laminate thinner.

[0102] Examples of the cured resin layer include films of cycloolefin polymer (COP), polyethylene terephthalate (PET), triacetyl cellulose (TAC), etc., which can also be used as a substrate described later, and cured products of compositions for forming cured resin layers containing polymerizable monomers. From the viewpoint of thinning, the cured resin layer is preferably a cured product of a composition for forming a cured resin layer. The cured resin layer may be composed of multiple layers, but from the viewpoint of productivity, it is preferably two layers or less, and more preferably a single layer. In addition, it is preferable that the cured resin layer is optically isotropic in terms of not affecting the optical properties of the multilayer.

[0103] In the present disclosure, the resin contained in the cured resin layer may be referred to based on the functional group having the largest number of functional groups contained therein. For example, when the functional groups contained in a resin have the largest number of acryloyloxy groups, the resin is called an acrylic resin, and when the functional groups contained in a resin have the largest number of epoxy groups, the resin is called an epoxy resin.

[0104] The cured resin layer preferably contains at least one selected from the group consisting of acrylic resin, epoxy resin, oxetane resin, urethane resin and melamine resin. By containing at least one of the above resins, the curability is high, and it is easy to improve the reliability when combined with the horizontally aligned liquid crystal cured film.

[0105] The composition for forming the cured resin layer that constitutes the cured resin layer is a composition containing a curable polymerizable monomer such as a radically polymerizable monomer, a cationic polymerizable monomer, or a thermally polymerizable monomer as a curable material, and it is more preferable that the composition contains a radically polymerizable monomer or a cationic polymerizable monomer, since this has a high reaction rate and improves productivity, and it is easy to improve reliability when combined with a horizontally aligned liquid crystal cured film.

[0106] The cured resin layer preferably contains at least one selected from the group consisting of acrylic resin, epoxy resin, oxetane resin, urethane resin, and melamine resin. By containing such a resin, the cured resin layer has high curability and is likely to improve reliability when combined with the horizontally aligned liquid crystal cured film.

[0107] The composition for forming the cured resin layer contains a curable polymerizable monomer as a curable material. Examples of the polymerizable monomer include a radical polymerizable monomer, a cationic polymerizable monomer, and a thermally polymerizable monomer. The polymerizable monomer is preferably a radical polymerizable monomer or a cationic polymerizable monomer because it has a high reaction rate, improves productivity, and is easy to improve reliability when combined with a horizontally aligned liquid crystal cured film.

[0108] Examples of such radical polymerizable monomers include (meth)acrylate compounds such as polyfunctional (meth)acrylate compounds, urethane (meth)acrylate compounds such as polyfunctional urethane (meth)acrylate compounds, epoxy (meth)acrylate compounds such as polyfunctional epoxy (meth)acrylate compounds, carboxyl group-modified epoxy (meth)acrylate compounds, polyester (meth)acrylate compounds, etc. These may be used alone or in combination of two or more.

[0109] From the viewpoint of improving reliability when combined with a horizontally aligned liquid crystal cured film, improving adhesion to adjacent layers, and improving productivity, the polymerizable monomer is preferably a polymerizable monomer having a (meth)acryloyloxy group, more preferably a polyfunctional (meth)acrylate compound, and even more preferably a polyfunctional acrylate compound.

[0110] Examples of polyfunctional acrylate compounds include difunctional (meth)acrylate monomers having two (meth)acryloyloxy groups in the molecule, and trifunctional or higher functional (meth)acrylate monomers having three or more (meth)acryloyloxy groups in the molecule.

[0111] In this specification, "(meth)acrylate" means "acrylate" or "methacrylate", "(meth)acryloyl" means "acryloyl" or "methacryloyl", and "polyfunctional (meth)acrylate compound" means a compound having two or more (meth)acryloyloxy groups in the molecule.

[0112] The polyfunctional (meth)acrylate compound may be used alone or in combination of two or more. When two or more polyfunctional (meth)acrylate compounds are used, the number of (meth)acryloyloxy groups contained in each polyfunctional (meth)acrylate compound may be the same or different.

[0113] Examples of monomers having two (meth)acryloyloxy groups in the molecule include alkylene glycol di(meth)acrylates such as ethylene glycol di(meth)acrylate, 1,3-butanediol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, and neopentyl glycol di(meth)acrylate; diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, di Polyoxyalkylene glycol di(meth)acrylates such as propylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, and polytetramethylene glycol di(meth)acrylate; di(meth)acrylates of halogen-substituted alkylene glycols such as tetrafluoroethylene glycol di(meth)acrylate; trimethylolpropane di(meth)acrylate, ditrimethylolpropane di(meth)acrylate, di(meth)acrylates of aliphatic polyols such as pentaerythritol di(meth)acrylate; di(meth)acrylates of hydrogenated dicyclopentadiene or tricyclodecane dialkanols such as hydrogenated dicyclopentadienyl di(meth)acrylate or tricyclodecane dimethanol di(meth)acrylate; di(meth)acrylates of dioxane glycols or dioxane dialkanols such as 1,3-dioxane-2,5-diyl di(meth)acrylate [also known as dioxane glycol di(meth)acrylate]; bisphenol di(meth)acrylates of alkylene oxide adducts of bisphenol A or bisphenol F, such as bisphenol A ethylene oxide adduct diacrylate and bisphenol F ethylene oxide adduct diacrylate; epoxy di(meth)acrylates of bisphenol A or bisphenol F, such as acrylic acid adduct of bisphenol A diglycidyl ether and acrylic acid adduct of bisphenol F diglycidyl ether; silicone di(meth)acrylates; di(meth)acrylates of hydroxypivalic acid neopentyl glycol ester;Examples of such compounds include 2,2-bis[4-(meth)acryloyloxyethoxyethoxyphenyl]propane; 2,2-bis[4-(meth)acryloyloxyethoxyethoxycyclohexyl]propane; 2-(2-hydroxy-1,1-dimethylethyl)-5-ethyl-5-hydroxymethyl-1,3-dioxane] di(meth)acrylate; and tris(hydroxyethyl)isocyanurate di(meth)acrylate.

[0114] Examples of monomers having three (meth)acryloyloxy groups in the molecule include glycerin tri(meth)acrylate, trimethylolpropane tri(meth)acrylate, ditrimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, a reaction product of pentaerythritol tri(meth)acrylate and an acid anhydride, caprolactone-modified trimethylolpropane tri(meth)acrylate, caprolactone-modified pentaerythritol tri(meth)acrylate, ethylene oxide-modified trimethylolpropane ... Examples of the monomer unit include ethylene oxide-modified pentaerythritol tri(meth)acrylate, propylene oxide-modified trimethylolpropane tri(meth)acrylate, propylene oxide-modified pentaerythritol tri(meth)acrylate, isocyanurate tri(meth)acrylate, a reaction product of caprolactone-modified pentaerythritol tri(meth)acrylate with an acid anhydride, a reaction product of ethylene oxide-modified pentaerythritol tri(meth)acrylate with an acid anhydride, and a reaction product of propylene oxide-modified pentaerythritol tri(meth)acrylate with an acid anhydride.

[0115] Examples of monomers having four (meth)acryloyloxy groups in the molecule include ditrimethylolpropane tetra(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol tetra(meth)acrylate, tripentaerythritol tetra(meth)acrylate, caprolactone-modified pentaerythritol tetra(meth)acrylate, caprolactone-modified tripentaerythritol tetra(meth)acrylate, ethylene oxide-modified pentaerythritol tetra(meth)acrylate, ethylene oxide-modified tripentaerythritol tetra(meth)acrylate, propylene oxide-modified pentaerythritol tetra(meth)acrylate, and propylene oxide-modified tripentaerythritol tetra(meth)acrylate.

[0116] Examples of monomers having five (meth)acryloyloxy groups in the molecule include dipentaerythritol penta(meth)acrylate, tripentaerythritol penta(meth)acrylate, a reaction product of dipentaerythritol penta(meth)acrylate with an acid anhydride, caprolactone-modified dipentaerythritol penta(meth)acrylate, caprolactone-modified tripentaerythritol penta(meth)acrylate, ethylene oxide-modified dipentaerythritol penta(meth)acrylate, ethylene oxide-modified tripentaerythritol penta(meth)acrylate, and the like. Examples of the compound include dipentaerythritol penta(meth)acrylate, propylene oxide-modified dipentaerythritol penta(meth)acrylate, propylene oxide-modified tripentaerythritol penta(meth)acrylate, a reaction product of caprolactone-modified dipentaerythritol penta(meth)acrylate with an acid anhydride, a reaction product of ethylene oxide-modified dipentaerythritol penta(meth)acrylate with an acid anhydride, and a reaction product of propylene oxide-modified dipentaerythritol penta(meth)acrylate with an acid anhydride.

[0117] Examples of monomers having six (meth)acryloyloxy groups in the molecule include dipentaerythritol hexa(meth)acrylate, tripentaerythritol hexa(meth)acrylate, caprolactone-modified dipentaerythritol hexa(meth)acrylate, caprolactone-modified tripentaerythritol hexa(meth)acrylate, ethylene oxide-modified dipentaerythritol hexa(meth)acrylate, ethylene oxide-modified tripentaerythritol hexa(meth)acrylate, propylene oxide-modified dipentaerythritol hexa(meth)acrylate, and propylene oxide-modified tripentaerythritol hexa(meth)acrylate.

[0118] Examples of monomers having seven (meth)acryloyloxy groups in the molecule include tripentaerythritol hepta(meth)acrylate, a reaction product of tripentaerythritol hepta(meth)acrylate and an acid anhydride, caprolactone-modified tripentaerythritol hepta(meth)acrylate, a reaction product of caprolactone-modified tripentaerythritol hepta(meth)acrylate and an acid anhydride, ethylene oxide-modified tripentaerythritol hepta(meth)acrylate, a reaction product of ethylene oxide-modified tripentaerythritol hepta(meth)acrylate and an acid anhydride, propylene oxide-modified tripentaerythritol hepta(meth)acrylate, and a reaction product of propylene oxide-modified tripentaerythritol hepta(meth)acrylate and an acid anhydride.

[0119] Examples of monomers having eight (meth)acryloyloxy groups in the molecule include tripentaerythritol octa(meth)acrylate, caprolactone-modified tripentaerythritol octa(meth)acrylate, ethylene oxide-modified tripentaerythritol octa(meth)acrylate, and propylene oxide-modified tripentaerythritol octa(meth)acrylate.

[0120] Examples of the cationic polymerizable monomer include an epoxy compound having an epoxy group and an oxetane compound having an oxetanyl group.

[0121] An epoxy compound is a polymerizable monomer having at least one epoxy group in the molecule. Examples of the epoxy compound include alicyclic epoxy compounds, aromatic epoxy compounds, and aliphatic epoxy compounds.

[0122] Alicyclic epoxy compounds are compounds having at least one epoxy group directly bonded to an alicyclic ring in the molecule. Examples of alicyclic epoxy compounds include 3,4-epoxycyclohexylmethyl 3,4-epoxycyclohexanecarboxylate, 3,4-epoxy-6-methylcyclohexylmethyl 3,4-epoxy-6-methylcyclohexanecarboxylate, ethylene bis(3,4-epoxycyclohexanecarboxylate), bis(3,4-epoxycyclohexylmethyl)adipate, bis(3,4-epoxy-6-methylcyclohexylmethyl)adipate, diethylene glycol bis(3,4-epoxycyclohexylmethyl ether), and ethylene glycol bis(3,4-epoxycyclohexylmethyl)ether. These alicyclic epoxy compounds can be used alone or in combination of two or more.

[0123] Aromatic epoxy compounds are compounds having an aromatic ring and an epoxy group in the molecule. Specific examples thereof include bisphenol-type epoxy compounds or oligomers thereof, such as diglycidyl ether of bisphenol A, diglycidyl ether of bisphenol F, and diglycidyl ether of bisphenol S; novolac-type epoxy resins, such as phenol novolac epoxy resin, cresol novolac epoxy resin, and hydroxybenzaldehyde phenol novolac epoxy resin; polyfunctional epoxy compounds, such as glycidyl ether of 2,2',4,4'-tetrahydroxydiphenylmethane and glycidyl ether of 2,2',4,4'-tetrahydroxybenzophenone; and polyfunctional epoxy resins, such as epoxidized polyvinylphenol. These aromatic epoxy compounds can be used alone or in combination of two or more.

[0124] The hydrogenated epoxy compounds are the nuclear hydrogenation products of the aromatic epoxy compounds. These can be produced by using polyhydric alcohols, typically hydrogenated bisphenols, as raw materials for the corresponding aromatic epoxy compounds, which are obtained by selectively hydrogenating the aromatic polyhydroxy compounds, typically bisphenols, in the presence of a catalyst under pressure, reacting the polyhydric alcohols with epichlorohydrin to form chlorohydrin ethers, which are then subjected to intramolecular ring closure with an alkali. These hydrogenated epoxy compounds can be used alone or in combination of two or more.

[0125] The aliphatic epoxy compound includes polyglycidyl ethers of aliphatic polyhydric alcohols or their alkylene oxide adducts. Specific examples thereof include diglycidyl ether of neopentyl glycol, diglycidyl ether of 1,4-butanediol, diglycidyl ether of 1,6-hexanediol, triglycidyl ether of glycerin, triglycidyl ether of trimethylolpropane, diglycidyl ether of polyethylene glycol, diglycidyl ether of propylene glycol, and polyglycidyl ethers of polyether polyols obtained by adding one or more alkylene oxides (ethylene oxide or propylene oxide) to aliphatic polyhydric alcohols such as ethylene glycol, propylene glycol, and glycerin. These aliphatic epoxy compounds can be used alone or in combination of two or more.

[0126] An oxetane compound is a compound containing at least one oxetanyl group in the molecule, and specific examples thereof include 3-ethyl-3-hydroxymethyloxetane (also called oxetane alcohol), 2-ethylhexyloxetane, 1,4-bis[{(3-ethyloxetan-3-yl)methoxy}methyl]benzene (also called xylylene bisoxetane), 3-ethyl-3[{(3-ethyloxetan-3-yl)methoxy}methyl]oxetane, 3-ethyl-3-(phenoxymethyl)oxetane, and 3-(cyclohexyloxy)methyl-3-ethyloxetane.

[0127] The above-mentioned thermally polymerizable monomer may, for example, be a melamine compound. Examples of the melamine compound include hexamethoxymethylmelamine, hexaethoxymethylmelamine, hexapropoxymethylmelamine, hexabutoxymethylmelamine, etc. The melamine compounds may be used alone or in combination of two or more.

[0128] Other polymerizable monomers include a combination of an isocyanate compound and an alcohol compound having a hydroxyl group in the molecule, and a urethane resin is produced. The isocyanate compound used in the production of urethane resin and urea resin usually has two or more isocyanato groups (-NCO) in the molecule, and various aromatic, aliphatic, or alicyclic diisocyanates can be used. Specific examples include tetramethylene diisocyanate, hexamethylene diisocyanate, isophorone diisocyanate, 2,4-tolylene diisocyanate, 4,4'-diphenyl diisocyanate, 1,5-naphthalene diisocyanate, 3,3'-dimethyl-4,4'-diphenyl diisocyanate, xylene diisocyanate, trimethylhexamethylene diisocyanate, 4,4'-diphenylmethane diisocyanate, and nuclear hydrogenation products of diisocyanates having aromatic rings among these. In addition, the alcohol compound used in the urethane resin usually has two or more hydroxyl groups in the molecule, and examples thereof include ethylene glycol, propylene glycol, 1,3-propanediol, diethylene glycol, dipropylene glycol, neopentyl glycol, 1,3-butanediol, 1,4-butanediol, 1,6-hexanediol, 1,9-nonanediol, 1,10-decanediol, 2,2,4-trimethyl-1,3-pentanediol, 3-methyl-1,5-pentanediol, neopentyl glycol ester of hydroxypivalic acid, 1,4-cyclohexanediol, spiroglycol, tricyclodecane dimethylol, bisphenol A, hydrogenated bisphenol A, trimethylolethane, trimethylolpropane, glycerin, 3-methylpentane-1,3,5-triol, pentaerythritol, dipentaerythritol, tripentaerythritol, and glucoses.

[0129] The above polymerizable monomers can be appropriately selected from the viewpoints of suppressing curling caused by heating during or after curing, improving processing characteristics, adjusting adhesion to the substrate or liquid crystal cured film, improving productivity, improving solvent resistance, and improving reliability when combined with a horizontally aligned liquid crystal cured film. In the present disclosure, the cured resin layer preferably contains at least one selected from the group consisting of acrylic resins, epoxy resins, oxetane resins, urethane resins, and melamine resins. In addition, for example, two or more radical polymerizable monomers may be used, or a radical polymerizable monomer and a cationic polymerizable monomer may be combined. In particular, it is preferable to contain a radical polymerizable monomer from the viewpoint of improving productivity.

[0130] The cured resin layer forming composition may further contain additives such as photopolymerization initiators, thermal polymerization initiators, solvents, antioxidants, photosensitizers, leveling agents, antioxidants, chain transfer agents, light stabilizers, tackifiers, fillers, flow control agents, plasticizers, defoamers, dyes, antistatic agents, and ultraviolet absorbers in addition to the polymerizable monomers. These additives are usually 0.1 to 15% by mass based on the mass of the solid content of the cured resin layer forming composition. The solid content of the cured resin layer forming composition means the total amount of components excluding the solvent from the composition when the cured resin layer forming composition contains a solvent.

[0131] In the composition for forming a cured resin layer, the content of the polymerizable monomer is preferably 50 parts by mass or more, more preferably 60 parts by mass or more, based on 100 parts by mass of the solid content of the composition. When in the above range, the reliability is easily improved when combined with a horizontally aligned liquid crystal cured film.

[0132] The composition for forming the cured resin layer preferably contains a polymerization initiator. Examples of the polymerization initiator include photopolymerization initiators and thermal polymerization initiators, but it is preferable to use a photopolymerization initiator from the viewpoint of improving productivity. The photopolymerization initiator is not particularly limited as long as it can initiate the curing of the polymerizable monomer by irradiation with active energy rays such as visible light, ultraviolet light, X-rays, and electron beams, and a photoradical polymerization initiator or a photocationic polymerization initiator can be appropriately used according to the type of polymerizable monomer. Specific examples of the photoradical polymerization initiator and the photocationic polymerization initiator include the same polymerization initiators as those exemplified above as those that can be blended in the polymerizable liquid crystal composition that forms the horizontally aligned liquid crystal cured film.

[0133] When the composition for forming a cured resin layer contains a polymerization initiator, the content of the polymerization initiator is preferably 0.1 to 10 parts by mass, more preferably 0.5 to 7 parts by mass, based on 100 parts by mass of the total amount of the curable compounds. When the content of the polymerization initiator is equal to or more than the lower limit, the polymerization initiation ability is fully expressed, and when the content of the polymerization initiator is equal to or less than the upper limit, the polymerization initiator is less likely to remain.

[0134] When the composition for forming a cured resin layer contains a solvent, the solvent can be appropriately selected depending on the viewpoint of sufficiently dissolving the polymerizable monomer and polymerization initiator added to the composition for forming a cured resin layer and the viewpoint of not dissolving the substrate, and for example, a solvent that can be used in a polymerizable liquid crystal composition for forming a horizontally aligned liquid crystal cured film can be used. The content of the solvent may be 1 to 10,000 parts by mass, preferably 10 to 1,000 parts by mass, more preferably 20 to 500 parts by mass, relative to 100 parts by mass of the total amount of the components contained in the composition for forming a cured resin layer.

[0135] In the laminate of the present disclosure, the cured resin layer is preferably optically isotropic. When the cured resin layer is optically isotropic, a laminate having high optical properties can be obtained when combined with the horizontally aligned liquid crystal cured film without affecting the optical properties of the horizontally aligned liquid crystal cured film.

[0136] When the laminate includes a cured resin layer, the order of lamination of the layers of the laminate can be appropriately selected, but the laminate preferably has a laminate structure including a horizontally aligned liquid crystal cured film, a horizontal alignment film, and a cured resin layer in this order. The laminate may further include a pressure-sensitive adhesive layer.

[0137] The laminate can be produced, for example, by a method comprising the following steps. Cured resin layer forming step: A step of forming a cured resin layer Horizontal alignment film formation process: A process for forming a horizontal alignment film Horizontal alignment liquid crystal cured film formation process: A process of forming a horizontal alignment liquid crystal cured film (optical film) on a horizontal alignment film.

[0138] (cured resin layer formation process) The cured resin layer can be obtained, for example, by applying the above-mentioned composition for forming a cured resin layer onto a substrate, then removing the solvent, if any, by drying, and curing the polymerizable monomer.

[0139] Examples of the substrate include glass substrates and film substrates, but resin film substrates are preferred from the viewpoint of processability. Examples of the resin constituting the film substrate include polyolefins such as polyethylene, polypropylene, and norbornene-based polymers; cyclic olefin resins; polyvinyl alcohol; polyethylene terephthalate; polymethacrylic acid esters; polyacrylic acid esters; cellulose esters such as triacetyl cellulose, diacetyl cellulose, and cellulose acetate propionate; polyethylene naphthalate; polycarbonate; polysulfone; polyether sulfone; polyether ketone; plastics such as polyphenylene sulfide and polyphenylene oxide. Such resins can be formed into a film by known means such as solvent casting and melt extrusion to form the substrate. The substrate surface (for example, the surface to be bonded to the adhesive layer) may be subjected to a surface treatment such as a release treatment such as silicone treatment, corona treatment, plasma treatment, etc.

[0140] Commercially available products may be used as the substrate. Examples of commercially available cellulose ester substrates include cellulose ester substrates manufactured by Fuji Photo Film Co., Ltd., such as Fujitac Film; cellulose ester substrates manufactured by Konica Minolta Opto Co., Ltd., such as "KC8UX2M", "KC8UY", and "KC4UY". Examples of commercially available cyclic olefin resins include cyclic olefin resins manufactured by Ticona (Germany), such as "Topas (registered trademark)", cyclic olefin resins manufactured by JSR Corporation, such as "Arton (registered trademark)", cyclic olefin resins manufactured by Zeon Corporation, such as "ZEONOR (registered trademark)" and "ZEONEX (registered trademark)", and cyclic olefin resins manufactured by Mitsui Chemicals, Inc., such as "Apel" (registered trademark). Commercially available cyclic olefin resin substrates may also be used. Commercially available cyclic olefin resin substrates include cyclic olefin resin substrates manufactured by Sekisui Chemical Co., Ltd., such as "S-Cina (registered trademark)" and "SCA40 (registered trademark)"; cyclic olefin resin substrates manufactured by Optes Inc., such as "ZEONORFILM (registered trademark)"; and cyclic olefin resin substrates manufactured by JSR Corporation, such as "ARTONFILM (registered trademark)."

[0141] From the viewpoints of thinning and ease of peeling of the substrate, the thickness of the substrate is usually 5 to 300 μm, and preferably 10 to 150 μm.

[0142] Examples of a method for applying the composition for forming a cured resin layer to a substrate or the like include known methods such as application methods such as spin coating, extrusion, gravure coating, die coating, bar coating, and applicator methods, and printing methods such as flexography.

[0143] When the composition for forming a cured resin layer contains a solvent, examples of the method for drying and removing the solvent include natural drying, ventilation drying, heat drying, and reduced pressure drying.

[0144] (Horizontal alignment film formation process) When the horizontal alignment film of the laminate is a rubbed alignment film, an alignment polymer composition is applied onto the cured resin layer, and the solvent is removed to form a coating film. The coating film is then rubbed to obtain the horizontal alignment film.

[0145] Examples of a method for applying the oriented polymer composition onto the cured resin layer include known methods such as application methods such as spin coating, extrusion, gravure coating, die coating, bar coating, and applicator methods, and printing methods such as flexography.

[0146] Examples of methods for drying and removing the solvent from the orientable polymer composition include natural drying, ventilation drying, heat drying, and reduced pressure drying.

[0147] The rubbing treatment may be carried out, for example, by contacting the coating film with a rotating rubbing roll wrapped with a rubbing cloth. If masking is performed during the rubbing treatment, a plurality of regions (patterns) having different orientation directions can be formed on the alignment film.

[0148] When the horizontal alignment film is a photo-alignment film, a composition for forming a photo-alignment film is applied onto the cured resin layer, and after removing the solvent, the composition is irradiated with polarized light to obtain the photo-alignment film. The polarized light to be irradiated is preferably polarized UV light.

[0149] As a method for applying the composition for forming a photo-alignment film onto the cured resin layer and a method for removing the solvent from the applied composition for forming a photo-alignment film, the same methods as those mentioned for the orientable polymer composition can be used.

[0150] The polarized light may be irradiated directly with polarized UV light after removing the solvent from the photo-alignment film-forming composition applied on the surface on which the horizontal alignment film is to be formed. In addition, it is particularly preferable that the polarized light is substantially parallel light. The wavelength of the polarized light to be irradiated is preferably in a wavelength range in which the photoreactive group of the polymer or monomer having a photoreactive group can absorb light energy. Specifically, UV (ultraviolet light) having a wavelength of 250 to 400 nm is preferable. Examples of light sources used for the polarized light irradiation include xenon lamps, high-pressure mercury lamps, ultra-high-pressure mercury lamps, metal halide lamps, ultraviolet lasers such as KrF and ArF, and high-pressure mercury lamps, ultra-high-pressure mercury lamps, and metal halide lamps are more preferable. Among these, high-pressure mercury lamps, ultra-high-pressure mercury lamps, and metal halide lamps are preferable because they have a high emission intensity of ultraviolet light with a wavelength of 313 nm. The polarized UV light can be irradiated by passing the light from the light source through an appropriate polarizer. As such a polarizer, a polarizing filter, a polarizing prism such as a Glan-Thompson or Glan-Taylor type polarizer, or a wire grid type polarizer can be used.

[0151] If masking is performed during rubbing or polarized light irradiation, a plurality of regions (patterns) in which the liquid crystal alignment directions are different can be formed.

[0152] Methods for obtaining a groove alignment film include a method in which the surface of a photosensitive polyimide film is exposed to light through an exposure mask having slits in a pattern shape, followed by development and rinsing to form a concave-convex pattern; a method in which a layer of uncured UV-curable resin is formed on a plate-shaped master having grooves on its surface, the formed resin layer is transferred to a cured resin layer, and then cured; and a method in which a roll-shaped master having multiple grooves is pressed against an uncured UV-curable resin film formed on a cured resin layer to form concave-convex patterns, and then cured.

[0153] When the laminate does not include a cured resin layer, a horizontal alignment film may be formed on the substrate.

[0154] (Horizontal alignment liquid crystal hardening film formation process) In this process, a polymerizable liquid crystal composition is applied onto the horizontal alignment film to obtain a coating film. The coating film obtained is heated to a temperature equal to or higher than the liquid crystal phase transition temperature of the polymerizable liquid crystal compound contained in the polymerizable liquid crystal composition. This dries and removes the solvent from the coating film, while aligning the polymerizable liquid crystal compound in the horizontal direction.

[0155] The heating temperature of the coating film can be appropriately determined in consideration of the materials of the polymerizable liquid crystal compound used and the substrate on which the coating film is formed. In order to make the polymerizable liquid crystal compound horizontally aligned while removing the solvent contained in the polymerizable liquid crystal composition, the heating temperature is preferably 3°C or higher, more preferably 5°C or higher than the liquid crystal phase (nematic phase) transition temperature of the polymerizable liquid crystal compound. The upper limit of the heating temperature is not particularly limited, but is preferably 180°C or lower, more preferably 150°C or lower, in order to avoid damage to the coating film and substrate due to heating. The nematic phase transition temperature can be measured using, for example, a polarizing microscope equipped with a temperature control stage, a differential scanning calorimeter (DSC), a thermogravimetric differential thermal analyzer (TG-DTA), or the like.

[0156] The heating time can be appropriately determined depending on the heating temperature, the type of polymerizable liquid crystal compound used, the type and boiling point of the solvent, and the amount thereof, etc. The heating time is, for example, 0.5 to 10 minutes, and preferably 0.5 to 5 minutes.

[0157] The removal of the solvent from the coating film may be performed simultaneously with heating to a temperature equal to or higher than the nematic phase transition temperature of the polymerizable liquid crystal compound, or may be performed separately, but it is preferable to perform the removal of the solvent simultaneously from the viewpoint of improving productivity. The removal of the solvent from the coating film is usually performed simultaneously with heating to a temperature equal to or higher than the nematic phase transition temperature of the polymerizable liquid crystal compound, but before heating to a temperature equal to or higher than the liquid crystal phase transition temperature of the polymerizable liquid crystal compound, a preliminary drying step may be provided to adequately remove the solvent in the coating film obtained from the polymerizable liquid crystal composition under conditions in which the polymerizable liquid crystal compound contained in the coating film is not polymerized. Examples of the drying method in the preliminary drying step include natural drying, ventilation drying, heat drying, and reduced pressure drying, and the drying temperature (heating temperature) in the drying step can be appropriately determined depending on the type of polymerizable liquid crystal compound used, the type of solvent, its boiling point, and its amount, etc.

[0158] Next, in the obtained dried coating film, the polymerizable liquid crystal compound is polymerized while maintaining the horizontal alignment state of the polymerizable liquid crystal compound, thereby forming a horizontally aligned liquid crystal cured film. The polymerization method is preferably a photopolymerization method, and a horizontally aligned liquid crystal cured film can be formed by irradiating light from the coated surface side of the polymerizable liquid crystal composition. In photopolymerization, the light irradiated to the dried coating film is appropriately selected according to the type of photopolymerization initiator contained in the dried coating film, the type of polymerizable liquid crystal compound (particularly, the type of polymerizable group possessed by the polymerizable liquid crystal compound) and the amount thereof. Specific examples thereof include one or more types of light selected from the group consisting of visible light, ultraviolet light, infrared light, X-rays, α-rays, β-rays and γ-rays, and active electron beams. Among them, ultraviolet light is preferred in that the progress of the polymerization reaction is easily controlled and that photopolymerization devices widely used in this field can be used. It is preferable to select the types of polymerizable liquid crystal compound and photopolymerization initiator contained in the polymerizable liquid crystal composition so that they can be photopolymerized by ultraviolet light. In addition, the polymerization temperature can be controlled by irradiating light while cooling the dried coating film with an appropriate cooling means during polymerization. By adopting such a cooling means, the polymerization of the polymerizable liquid crystal compound can be carried out at a lower temperature, and even if a substrate having a relatively low heat resistance is used, a horizontally aligned liquid crystal cured film can be appropriately formed.

[0159] Examples of light sources for active energy rays include low-pressure mercury lamps, medium-pressure mercury lamps, high-pressure mercury lamps, ultra-high-pressure mercury lamps, xenon lamps, halogen lamps, carbon arc lamps, tungsten lamps, gallium lamps, excimer lasers, LED light sources emitting light in the wavelength range of 380 to 440 nm, chemical lamps, black light lamps, microwave-excited mercury lamps, and metal halide lamps.

[0160] The ultraviolet irradiation intensity is, for example, 10 to 3,000 mW / cm 2The time for light irradiation is, for example, 0.1 seconds to 10 minutes, preferably 0.1 seconds to 5 minutes, more preferably 0.1 seconds to 3 minutes, and even more preferably 0.1 seconds to 1 minute. When irradiation is performed once or multiple times with such ultraviolet irradiation intensity, the integrated light amount is, for example, 10 to 3,000 mJ / cm. 2 , preferably 50 to 2,000 mJ / cm 2 , more preferably 100 to 1,000 mJ / cm 2 It is.

[0161] When the laminate further comprises a pressure-sensitive adhesive layer, examples of the pressure-sensitive adhesive constituting the layer include a pressure-sensitive adhesive, a drying-solidifying adhesive, and a chemically reactive adhesive. Examples of the chemically reactive adhesive include an active energy ray-curing adhesive.

[0162] The pressure-sensitive adhesive usually contains a polymer and may contain a solvent. Examples of the polymer include an acrylic polymer, a silicone polymer, a polyester, a polyurethane, and a polyether. Among them, an acrylic adhesive containing an acrylic polymer is preferable because it has excellent optical transparency, moderate wettability and cohesive strength, excellent adhesion, and further has high weather resistance and heat resistance, and is unlikely to lift or peel under heating or humidifying conditions.

[0163] As the acrylic polymer, a copolymer of a (meth)acrylate in which the alkyl group in the ester moiety is an alkyl group having 1 to 20 carbon atoms, such as a methyl group, an ethyl group, or a butyl group, and a (meth)acrylic monomer having a functional group, such as (meth)acrylic acid or hydroxyethyl (meth)acrylate, is preferred.

[0164] A pressure-sensitive adhesive containing such a copolymer is preferable because it has excellent adhesion and can be removed relatively easily after being attached to a transfer-receiving object without leaving any adhesive residue on the transfer-receiving object. The glass transition temperature of the acrylic polymer is preferably 25° C. or lower, more preferably 0° C. or lower. The mass average molecular weight of such an acrylic polymer is preferably 100,000 or higher.

[0165] Examples of the solvent include the same solvents as those usable in the polymerizable liquid crystal composition. The pressure-sensitive adhesive may contain a light diffusing agent. The light diffusing agent is an additive that imparts light diffusibility to the adhesive, and may be fine particles having a refractive index different from that of the polymer contained in the adhesive. Examples of the light diffusing agent include fine particles made of inorganic compounds and fine particles made of organic compounds (polymers). Many of the polymers contained as active ingredients in the adhesive, including acrylic polymers, have a refractive index of 1.4 to 1.6, so it is preferable to appropriately select a light diffusing agent from among those having a refractive index of 1.2 to 1.8. The difference in refractive index between the polymer contained as an active ingredient in the adhesive and the light diffusing agent is usually 0.01 or more, and from the viewpoint of the brightness and display properties of the display device, it is preferably 0.01 to 0.2. The fine particles used as the light diffusing agent are preferably spherical fine particles, more preferably near monodisperse fine particles, and more preferably fine particles having an average particle size of 2 to 6 μm. The refractive index is measured by a general minimum deviation method or Abbe refractometer.

[0166] Examples of fine particles made of inorganic compounds include aluminum oxide (refractive index 1.76) and silicon oxide (refractive index 1.45). Examples of fine particles made of organic compounds (polymers) include melamine beads (refractive index 1.57), polymethyl methacrylate beads (refractive index 1.49), methyl methacrylate / styrene copolymer resin beads (refractive index 1.50 to 1.59), polycarbonate beads (refractive index 1.55), polyethylene beads (refractive index 1.53), polystyrene beads (refractive index 1.6), polyvinyl chloride beads (refractive index 1.46), and silicone resin beads (refractive index 1.46). The content of the light diffusing agent is, for example, 3 to 30 parts by mass with respect to 100 parts by mass of the polymer.

[0167] The thickness of the pressure-sensitive adhesive is not particularly limited since it is determined according to its adhesive strength, etc., but is, for example, 1 μm to 40 μm. From the viewpoint of processability, durability, etc., the thickness is preferably 3 μm to 25 μm, more preferably 5 μm to 20 μm. By setting the thickness of the pressure-sensitive adhesive layer formed from the adhesive to 5 μm to 20 μm, it is possible to maintain brightness when the display device is viewed from the front or obliquely, and to prevent bleeding or blurring of the displayed image.

[0168] The dry-solidifying adhesive may contain a solvent. Examples of the dry-solidifying adhesive include compositions containing a polymer of a monomer having a protonic functional group such as a hydroxyl group, a carboxyl group, or an amino group and an ethylenically unsaturated group or a urethane resin as a main component, and further containing a crosslinking agent or a curing compound such as a polyhydric aldehyde, an epoxy compound, an epoxy resin, a melamine compound, a zirconia compound, or a zinc compound. Examples of the polymer of a monomer having a protonic functional group such as a hydroxyl group, a carboxyl group, or an amino group and an ethylenically unsaturated group include ethylene-maleic acid copolymers, itaconic acid copolymers, acrylic acid copolymers, acrylamide copolymers, saponified polyvinyl acetate, and polyvinyl alcohol resins.

[0169] Examples of the polyvinyl alcohol resin include polyvinyl alcohol, partially saponified polyvinyl alcohol, fully saponified polyvinyl alcohol, carboxyl group-modified polyvinyl alcohol, acetoacetyl group-modified polyvinyl alcohol, methylol group-modified polyvinyl alcohol, and amino group-modified polyvinyl alcohol, etc. The content of the polyvinyl alcohol resin in the aqueous pressure-sensitive adhesive is, for example, 1 to 10 parts by mass, and preferably 1 to 5 parts by mass, relative to 100 parts by mass of water.

[0170] Examples of the urethane resin include polyester ionomer urethane resin. The polyester ionomer urethane resin referred to here is a urethane resin having a polyester skeleton, into which a small amount of an ionic component (hydrophilic component) is introduced. The ionomer urethane resin is emulsified in water to form an emulsion without using an emulsifier, and can be used as a water-based adhesive. When using a polyester ionomer urethane resin, it is effective to add a water-soluble epoxy compound as a crosslinking agent.

[0171] Examples of epoxy resins include polyamide epoxy resins obtained by reacting epichlorohydrin with polyamide polyamines obtained by reacting polyalkylene polyamines such as diethylenetriamine or triethylenetetramine with dicarboxylic acids such as adipic acid. Commercially available products of such polyamide epoxy resins include Sumirez Resin (registered trademark) 650 and Sumirez Resin 675 (both manufactured by Sumika Chemtex Corporation), and WS-525 (manufactured by Nippon PMC Corporation). When an epoxy resin is blended, the amount of the epoxy resin added is, for example, 1 to 100 parts by mass, preferably 1 to 50 parts by mass, relative to 100 parts by mass of the polyvinyl alcohol resin.

[0172] The thickness of the adhesive layer formed from the dry-setting adhesive is, for example, 0.001 to 5 μm, preferably 0.01 to 2 μm, and more preferably 0.01 to 0.5 μm. If the adhesive layer formed from the dry-setting adhesive is too thick, the appearance is likely to be poor.

[0173] The active energy ray curable adhesive may contain a solvent. The active energy ray curable adhesive is an adhesive that is cured by irradiation with active energy rays. Examples of the active energy ray curable adhesive include a cationic polymerizable adhesive containing an epoxy compound and a cationic polymerization initiator, a radical polymerizable adhesive containing an acrylic curing component and a radical polymerization initiator, an adhesive containing both a cationic polymerizable curing component such as an epoxy compound and a radical polymerizable curing component such as an acrylic compound, and further containing a cationic polymerization initiator and a radical polymerization initiator, and an adhesive that does not contain these polymerization initiators and is cured by irradiation with an electron beam.

[0174] The active energy ray curable adhesive is preferably a radically polymerizable active energy ray curable adhesive containing an acrylic curing component and a photoradical polymerization initiator, or a cationic polymerizable active energy ray curable adhesive containing an epoxy compound and a photocationic polymerization initiator. Examples of the acrylic curing component include (meth)acrylates such as methyl (meth)acrylate and hydroxyethyl (meth)acrylate, and (meth)acrylic acid. The active energy ray curable adhesive containing an epoxy compound may further contain a compound other than the epoxy compound. Examples of the compound other than the epoxy compound include an oxetane compound and an acrylic compound.

[0175] Examples of the photoradical polymerization initiator and photocationic polymerization initiator include the above-mentioned photoradical polymerization initiator and photocationic polymerization initiator. The content of the radical polymerization initiator and the cationic polymerization initiator is, for example, 0.5 to 20 parts by mass, and preferably 1 to 15 parts by mass, relative to 100 parts by mass of the active energy ray-curable adhesive.

[0176] The active energy ray-curable adhesive may further contain an ion trapping agent, an antioxidant, a chain transfer agent, a tackifier, a thermoplastic resin, a filler, a flow control agent, a plasticizer, an antifoaming agent, and the like.

[0177] In this specification, active energy rays are defined as energy rays that can decompose a compound that generates active species to generate active species.Such active energy rays include visible light, ultraviolet light, infrared light, X-rays, α-rays, β-rays, γ-rays and electron beams, etc., and ultraviolet light and electron beams are preferred.Preferred ultraviolet light irradiation conditions are the same as those for the polymerization of the above-mentioned polymerizable liquid crystal compound.

[0178] The laminate may include other layers such as a vertically aligned liquid crystal cured film or other aligned liquid crystal cured films.

[0179] [Polarizing plate] The polarizing plate according to this embodiment includes a polarizing film and the optical film according to the above embodiment. The polarizing plate may include a polarizing film and the laminate according to the above embodiment.

[0180] (Polarizing film) The polarizing film is a film having a polarizing function, and examples of the polarizing film include a stretched film having a dye having anisotropy adsorbed thereon, a film coated with a dye having anisotropy, and the like, which includes a polarizer, etc. Examples of the dye having anisotropy include a dichroic dye.

[0181] The polarizer may be produced, for example, through the following steps (1) to (4), whereby a stretched film having a dye having absorption anisotropy adsorbed thereon is obtained as a polarizer. Step (1): A step of uniaxially stretching a polyvinyl alcohol-based resin film Step (2): A step of dyeing a polyvinyl alcohol-based resin film with a dichroic dye to adsorb the dichroic dye. Step (3): A step of treating the polyvinyl alcohol resin film having the dichroic dye adsorbed thereon with an aqueous boric acid solution. Step (4): A step of washing with water after treatment with an aqueous boric acid solution

[0182] Polyvinyl alcohol resins are obtained by saponifying polyvinyl acetate resins. As polyvinyl acetate resins, in addition to polyvinyl acetate, which is a homopolymer of vinyl acetate, copolymers of vinyl acetate and other monomers copolymerizable therewith are used. Examples of other monomers copolymerizable with vinyl acetate include unsaturated carboxylic acids, olefins, vinyl ethers, unsaturated sulfonic acids, and acrylamides having an ammonium group.

[0183] The saponification degree of the polyvinyl alcohol resin is, for example, 85 to 100 mol%, preferably 98 mol% or more. The polyvinyl alcohol resin may be modified, and for example, polyvinyl formal or polyvinyl acetal modified with aldehydes can also be used. The polymerization degree of the polyvinyl alcohol resin is, for example, 1,000 to 10,000, preferably 1,500 to 5,000.

[0184] Such a polyvinyl alcohol-based resin is used as a raw film for a polarizing film. The method for forming a film of the polyvinyl alcohol-based resin is not particularly limited, and the film can be formed by a known method. The thickness of the polyvinyl alcohol-based raw film can be, for example, 10 to 150 μm.

[0185] The uniaxial stretching of the polyvinyl alcohol-based resin film can be performed before, simultaneously with, or after dyeing with a dichroic dye. When the uniaxial stretching is performed after dyeing, the uniaxial stretching may be performed before or during the boric acid treatment. It is also possible to perform the uniaxial stretching at these multiple stages. In the uniaxial stretching, the film may be uniaxially stretched between rolls having different peripheral speeds, or may be uniaxially stretched using a heated roll. The uniaxial stretching may be dry stretching in which the film is stretched in the air, or wet stretching in which the film is stretched in a swollen state using a solvent. The stretching ratio is, for example, 3 to 8 times.

[0186] Dyeing of a polyvinyl alcohol-based resin film with a dichroic dye is carried out, for example, by a method of immersing the polyvinyl alcohol-based resin film in an aqueous solution containing the dichroic dye.

[0187] Specifically, iodine or a dichroic organic dye is used as the dichroic pigment. Examples of the dichroic organic dye include a dichroic direct dye made of a disazo compound such as CIDIRECT RED 39, and a dichroic direct dye made of a compound such as trisazo or tetrakisazo. It is preferable that the polyvinyl alcohol resin film is immersed in water before the dyeing process.

[0188] When iodine is used as the dichroic dye, a method of dyeing a polyvinyl alcohol-based resin film by immersing it in an aqueous solution containing iodine and potassium iodide is usually adopted. The content of iodine in this aqueous solution is, for example, 0.01 to 1 part by mass per 100 parts by mass of water. The content of potassium iodide is, for example, 0.5 to 20 parts by mass per 100 parts by mass of water. The temperature of the aqueous solution used for dyeing is, for example, 20 to 40°C. The immersion time in this aqueous solution (dyeing time) is, for example, 20 to 1,800 seconds.

[0189] On the other hand, when a dichroic organic dye is used as the dichroic pigment, for example, a method of dyeing a polyvinyl alcohol resin film by immersing it in an aqueous solution containing a water-soluble dichroic dye is adopted. The content of the dichroic organic dye in this aqueous solution is, for example, 1×10 -4 ~10 parts by mass, preferably 1 × 10 -3 ~1 part by mass, more preferably 1 × 10 -3 ~1×10 -2 The amount is parts by mass. This aqueous solution may contain an inorganic salt such as sodium sulfate as a dyeing assistant. The temperature of the dichroic dye aqueous solution used for dyeing is, for example, 20 to 80° C. The immersion time in this aqueous solution (dyeing time) is, for example, 10 to 1,800 seconds.

[0190] The boric acid treatment after dyeing with a dichroic dye can be carried out, for example, by immersing the dyed polyvinyl alcohol-based resin film in an aqueous boric acid solution. The content of boric acid in this aqueous boric acid solution is, for example, 2 to 15 parts by mass, preferably 5 to 12 parts by mass, per 100 parts by mass of water. When iodine is used as the dichroic dye, this aqueous boric acid solution preferably contains potassium iodide, and in this case, the content of potassium iodide is, for example, 0.1 to 15 parts by mass, preferably 5 to 12 parts by mass, per 100 parts by mass of water. The immersion time in the aqueous boric acid solution is, for example, 60 to 1,200 seconds, preferably 150 to 600 seconds, and more preferably 200 to 400 seconds. The temperature of the boric acid treatment is, for example, 50°C or higher, preferably 50 to 85°C, and more preferably 60 to 80°C.

[0191] The polyvinyl alcohol-based resin film after the boric acid treatment may be washed with water. The washing can be performed, for example, by immersing the boric acid-treated polyvinyl alcohol-based resin film in water. The temperature of the water used in the washing is, for example, 5 to 40° C. The immersion time is, for example, 1 to 120 seconds.

[0192] After washing with water, a drying treatment is carried out to obtain a polarizer. The drying treatment can be carried out, for example, using a hot air dryer or a far infrared heater. The temperature of the drying treatment is, for example, 30 to 100°C, and preferably 50 to 80°C. The time of the drying treatment is, for example, 60 to 600 seconds, and preferably 120 to 600 seconds. The moisture content of the polarizer is reduced to a practical level by the drying treatment. The moisture content is, for example, 5 to 20% by weight, and preferably 8 to 15% by weight. If the moisture content is less than 5% by weight, the polarizer loses its flexibility, and the polarizer may be damaged or broken after drying. If the moisture content exceeds 20% by weight, the thermal stability of the polarizer may be deteriorated.

[0193] The thickness of the polarizer is preferably 5 to 40 μm.

[0194] Examples of the film coated with a dye having absorption anisotropy include a film obtained by coating a composition containing a dichroic dye having liquid crystal properties or a composition containing a dichroic dye and a polymerizable liquid crystal. The film preferably has a protective film on one or both sides. Examples of the protective film include the same as the substrate exemplified above.

[0195] The film coated with the dye having absorption anisotropy is preferably thin, but if it is too thin, the strength decreases and the processability tends to be poor. The thickness of the film is, for example, 20 μm or less, preferably 5 μm or less, and more preferably 0.5 to 3 μm.

[0196] Specific examples of the film coated with a dye having the above-mentioned absorption anisotropy include the films described in JP-A-2012-33249 and the like.

[0197] The polarizing film may include a transparent protective film. The transparent protective film is attached to at least one surface of the polarizer with an adhesive. As the transparent protective film, the same transparent film as the above-mentioned substrate can be preferably used.

[0198] The polarizing plate according to this embodiment can be obtained, for example, by laminating the optical film or laminate according to the above embodiment and a polarizing film via an adhesive layer or the like.

[0199] The polarizing plate according to this embodiment may transmit linearly polarized light, circularly polarized light, or elliptically polarized light.

[0200] When the polarizing plate is a linear polarizer, the optical film according to the above embodiment and the polarizing film are preferably laminated such that the angle between the slow axis (optical axis) of the optical film and the absorption axis of the polarizing film is 0±5° or 90±5°. When the polarizing plate is a circular polarizer, the optical film according to the above embodiment and the polarizing film are preferably laminated such that the angle between the slow axis (optical axis) of the optical film and the absorption axis of the polarizing film is 45±5°.

[0201] The polarizing plate according to this embodiment may include, for example, an adhesive layer (sheet) for attaching the polarizing plate to a display element such as an organic EL display, a protective film used for the purpose of protecting the surface of a polarizer or optical film from scratches or dirt, and the like.

[0202] [Image display device] The image display device according to this embodiment includes the polarizing plate according to the above embodiment. The image display device is a device having a display element, and includes a light-emitting element or a light-emitting device as a light source. The image display device may be, for example, a liquid crystal display device, an organic electroluminescence (EL) display device, an inorganic electroluminescence (EL) display device, a touch panel display device, an electron emission display device (e.g., a field emission display device (FED) or a surface field emission display device (SED)), electronic paper (a display device using electronic ink or an electrophoretic element, a plasma display device, a projection display device (e.g., a grating light valve (GLV) display device, a display device having a digital micromirror device (DMD)), or a piezoelectric ceramic display.

[0203] The liquid crystal display device includes any of a transmissive liquid crystal display device, a semi-transmissive liquid crystal display device, a reflective liquid crystal display device, a direct-view liquid crystal display device, and a projection liquid crystal display device. These display devices may be display devices that display two-dimensional images, or stereoscopic display devices that display three-dimensional images. The polarizing plate according to the present embodiment can be suitably used in organic electroluminescence (EL) display devices and inorganic electroluminescence (EL) display devices, and the optical film according to the present embodiment can be suitably used in liquid crystal display devices and touch panel display devices. These display devices can exhibit good image display characteristics by being provided with the polarizing plate according to the above embodiment, which has high reliability. EXAMPLES

[0204] The present disclosure will be described in more detail below based on examples and comparative examples, but the present disclosure is not limited to the following examples. In the examples, "%" and "parts" mean mass% and mass parts, respectively, unless otherwise specified.

[0205] [Examples 1 to 8 and Comparative Example 1] (Preparation of composition for forming photoalignment film) The photoalignment polymer (weight average molecular weight: 50,000, m:n = 50:50) having the structure shown below was produced in accordance with the method described in JP 2021-196514 A. Two parts of the photoalignment polymer and 98 parts of cyclopentanone (solvent) were mixed as components to obtain a mixture. The mixture was stirred at 80 ° C. for 1 hour to prepare a composition for forming a photoalignment film. Photoalignable materials: [ka]

[0206] (Production of polymerizable liquid crystal compounds) The polymerizable liquid crystal compound (P1) and the polymerizable liquid crystal compound (P2) having the structures shown below were prepared. The polymerizable liquid crystal compound (P1) was prepared in the same manner as described in JP-A-2019-003177. The polymerizable liquid crystal compound (P2) was prepared in the same manner as described in JP-A-2009-173893. Polymerizable liquid crystal compound (P1): [ka] Polymerizable liquid crystal compound (P2): [ka]

[0207] A solution was obtained by dissolving 1 mg of the polymerizable liquid crystal compound (P1) in 10 mL of chloroform. The obtained solution was placed in a measurement cell with an optical path length of 1 cm, and the measurement sample was set in an ultraviolet-visible spectrophotometer (Shimadzu Corporation, "UV-2450") to measure the absorption spectrum. The wavelength at which the maximum absorbance was obtained was read from the obtained absorption spectrum, and the maximum absorption wavelength λmax in the wavelength range of 300 to 400 nm was 356 nm.

[0208] (Preparation of Polymerizable Liquid Crystal Composition) A polymerizable liquid crystal compound (P1) and a polymerizable liquid crystal compound (P2) were mixed in a mass ratio (P1:P2) of 90:10 to obtain a mixture. 0.1 parts by mass of a leveling agent "BYK-361N" (manufactured by BM Chemie) and additive A were added to 100 parts by mass of the mixture. The amount of additive A added to 100 parts by mass was set to the value shown in Table 1. In Table 1, when two types of compounds were used as additive A, the respective compounds are shown in the upper and lower rows of the column for the type of additive A. The value in the upper row of the column for the amount of additive A added indicates the amount of the compound in the upper row of the column for the type of additive A added. The value in the lower row of the column for the amount of additive A added indicates the amount of the compound in the lower row of the column for the type of additive A added. The abbreviations in Table 1 are as follows.

[0209] Compound (A31): Compound represented by the above formula (A31) (CLogP: 9.5155) Compound (A32): Compound represented by the above formula (A32) (CLogP: 13.7112) Compound (C1): A compound represented by the following formula (C1) (CLogP: 3.8153)

[0210] [ka]

[0211] N-methyl-2-pyrrolidone (NMP) was further added to the mixture so that the solid content (polymerizable liquid crystal compounds (P1), (P2), additive A and leveling agent) concentration was 13%. The mixture was stirred at a temperature of 80° C. for 1 hour to prepare a polymerizable liquid crystal composition.

[0212] (Preparation of Laminate) A biaxially oriented polyethylene terephthalate (PET) film (Diafoil, manufactured by Mitsubishi Plastics, Inc.) was prepared as a substrate. The above-mentioned composition for forming a photo-alignment film was applied to one surface of the substrate using a bar coater. The obtained coating film was dried at 120°C for 2 minutes, and then cooled to room temperature to form a dry film. Then, a UV irradiation device (SPOT CURE SP-9, manufactured by Ushio Inc.) was used to irradiate 100 mJ of polarized ultraviolet light (based on 313 nm) to obtain a photo-alignment film. The thickness of the photo-alignment film measured using an ellipsometer M-220 manufactured by JASCO Corporation was 100 nm.

[0213] A polymerizable liquid crystal composition was applied onto the obtained photo-alignment film using a bar coater to form a coating film. This coating film was dried by heating at 120°C for 2 minutes, and then cooled to room temperature to obtain a dried film. Next, a high-pressure mercury lamp ("Uniquer VB-15201BY-A" manufactured by Ushio Inc.) was used to expose the film to light in a nitrogen atmosphere at a dose of 500 mJ / cm. 2 The dried film was irradiated with ultraviolet light (365 nm standard) to form a horizontally aligned liquid crystal cured film (optical film). This resulted in a laminate consisting of a substrate / photo-aligned film / horizontally aligned liquid crystal cured film. The polymerizable liquid crystal compound was cured in a state of being aligned horizontally relative to the substrate surface. The thickness of the optical film was measured using a laser microscope LEXT OLS4100 manufactured by Olympus Corporation and was 2.0 μm.

[0214] (Preparation of the first test piece) The laminate was cut to a size of 4 cm x 4 cm. The surface of the laminate on the optical film side was corona-treated once (output: 0.3 kW, treatment speed: 3 m / min) using a corona treatment device (AGF-B10, manufactured by Kasuga Electric Co., Ltd.). The laminate and glass were bonded together via a pressure-sensitive adhesive (manufactured by Lintec Corporation, thickness: 25 μm). The laminate was bonded so that the corona-treated surface and the glass faced each other. The substrate (PET film) was peeled off and removed from the laminate to obtain a first test piece (layer structure: glass / adhesive / optical film / photo-alignment film).

[0215] (Heat treatment) The first test piece was left to stand for 30 minutes in a drying oven set at 100° C. Thereafter, the first test piece was removed from the oven and left to stand for 1 hour in an environment of 25° C. and humidity 55%.

[0216] (Measurement of in-plane retardation value of optical film using first test piece) The in-plane retardation value of the optical film was measured using the first test piece before the heat treatment. For the measurement, KOBRA-WR manufactured by Oji Scientific Instruments Co., Ltd. was used. The wavelengths of light were 448.2 nm, 498.6 nm, 548.4 nm, 587.3 nm, 628.7 nm, and 748.6 nm. From the measurement results of these wavelengths, the in-plane retardation values ​​for light with wavelengths of 450 nm, 550 nm, and 630 nm were calculated using Cauchy's dispersion formula. The results are shown in Table 1.

[0217] The in-plane retardation value Re(550) of the optical film was determined using the first test piece after the heat treatment in the same manner as the optical film before the heat treatment. The change in the in-plane retardation value Re(550) before and after the heat treatment (ΔRe(550)) was evaluated according to the following criteria. The results are shown in Table 1.

[0218] (standard) A: Less than 4 nm B: 4nm or more and less than 5nm C: 5nm or more

[0219] (Measurement of the content of compound (A)) The content of compound (A) per unit volume of the optical film was measured. Specifically, about 3 to 4 mg of the optical film was collected by scraping the first test piece from the photo-alignment film side with a spatula. The collected optical film was added to 2 mL of THF (tetrahydrofuran) and left for 24 hours. As a result, an extract in which the target component was extracted in THF was obtained. The extract was subjected to HPLC measurement under the following conditions to perform a quantitative analysis of compound (A). From the results of the quantitative analysis, the content of compound (A) per unit volume of the optical film was calculated. The results are shown in Table 1.

[0220] <HPLC Measurement Conditions> Measuring device: HPLC LC-10AT (manufactured by Shimadzu Corporation) Column: L-column ODS (length: 105 mm, inner diameter 3 mm, particle size 3 μm) Flow rate: 0.5 mL / min Injection volume: 5 μL Detection wavelengths: 254 nm, 350 nm Mobile phase A: Water with 0.1% (v / v) TFA (trifluoroacetic acid) added Mobile phase B: Acetonitrile Stabilization time: 15 minutes Gradient conditions: 70% - 100% mobile phase B for 30 minutes, followed by 100% mobile phase B for 30 minutes

[0221]

Table 1

Claims

1. The present invention includes a compound (A) having a skeleton represented by the following general formula (A1) as a partial structure, The content of the compound (A) per unit volume is 1.5 kg / m 3 More than 20kg / m 3 The following is an optical film. 【Chemistry 1】 [In formula (A1), R 1 represents a hydrogen atom, a hydrocarbon group, or a carbonyl group.

2. The optical film according to claim 1 , which satisfies the following formulas (1) and (2): 0.82≦Re(450) / Re(550)≦0.98 (1) 100 nm≦Re(550)≦160 nm (2) [In the formula, Re(450) represents an in-plane retardation value for light having a wavelength of 450 nm, and Re(550) represents an in-plane retardation value for light having a wavelength of 550 nm.]

3. The optical film according to claim 2 , which has a thickness of 0.5 μm or more and 5 μm or less.

4. The optical film according to claim 1 , comprising a cured product of a polymerizable liquid crystal compound.

5. A polarizing plate comprising a polarizing film and the optical film according to any one of claims 1 to 4.

6. An image display device comprising the polarizing plate according to claim 5 .

Citation Information

Patent Citations

  • Method for producing polycarbonate, and transparent film

    JP2012214801A